PENGARUH FASILITAS KANTOR TERHADAP MOTIVASI KERJA PEGAWAI PUSKESMAS HERLANG KABUPATEN BULUKUMBA - Abdul Rauf Alhayra; Zainal Ruma; Uhud Darmawan Natsir (Transpublika Publisher, 2022)
This research is a research that aims to find out how the effect of office facilities on work motivation of Herlang Health Center employees, Bulukumba Regency. This research uses a quantitative approach. The population in this study were all employees of the Herlang Health Center, totaling 86 employees. The technique for determining the sample used a saturated sample, namely all employees of the Herlang Health Center, totaling 86 employees, were sampled. There are 2 variables in this study, namely the independent variable of office facilities (X) and the dependent variable of work motivation (Y). Data collection techniques are carried out by observation, distributing questionnaires (questionnaires), interviews, and documentation. The analytical technique used is simple linear regression using SPSS 21 (statistical package for social sciences) as a tool. The results of research that has been carried out at the Herlang Health Center, Bulukumba Regency, the data obtained from research findings that there is a significant influence between office facilities on employee motivation at Herlang Health Center is 73.7%